Treatment of refractory post-esophagectomy anastomotic esophageal strictures using temporary fully covered esophageal metal stenting compared to repeated bougie dilation: results of a randomized controlled trial - Kappelle, W. F.; van Hooft, J. E.; Spaander, M. C. W.; Vleggaar, F. P.; Bruno, M. J.; Maluf-Filho, F.; Bogte, A.; van Halsema, E.; Siersema, P. D. (Endoscopy International Open, 2019)
Background and study aims Fully covered self-expanding metal stents (FCSEMS) provide an alternative to bougie dilation (BD) for refractory benign esophageal strictures. Controlled studies comparing temporary placement of FCSES to repeated BD are not available.Patients and methods Patients with refractory anastomotic esophageal strictures, dysphagia scores ≥ 2, and two to five prior BD were randomized to 8 weeks of FCSEMS or to repeated BD. The primary endpoint was the number of BD during the 12 months after baseline treatment. Results Eighteen patients were included (male 67 %, median age 66.5; 9 received metal stents, 9 received BD). Technical success rate of stent placement and stent removal was 100 %. Recurrent dysphagia occurred in 13 patients (72 %) during follow-up. No significant difference was found between the stent and BD groups for mean number of BD during follow-up (5.4 vs. 2.4, P = 0.159), time to recurrent dysphagia (median 36 days vs. 33 days, Kaplan-Meier: P = 0.576) and frequency of reinterventions per month (median 0.3 vs. 0.2, P = 0.283). Improvement in quality of life score was greater in the stent group compared to the BD group at month 12 (median 26 % vs. 4 %, P = 0.011). Conclusions The current data did not provide evidence for a statistically significant difference between the two groups in the number of BD during the 12 months after initial treatment. Metal stenting offers greater improvement in quality of life from baseline at 12 months compared to repeated BD for patients with refractory anastomotic esophageal strictures.